Does Green Accounting Matter As a Determinant Of Financial Reporting Quality? A Bibliometric Literature Review - Sari Indra Pratama; Totok Dewayanto (Garuda Prestasi Nusantara Consulting, 2025)
This study aims to analyze research trends on whether the quality of financial Reporting will increase with the implementation of green accounting practices. This is an effort to raise corporate awareness of the environment in this growing era which is reflected in the quality of transparent and accountable financial statements. This research was conducted with a Bibliometric study on the Scopus database peridoe 2019-2024. The keywords used are “Green Accounting” and “Quality of Financial Statement” to produce a more specific data search according to the research theme category with 547 articles. The findings show that the increasing trend of publications on the application of green accounting practices can improve the Quality of Financial Reporting with an average of 10% per year and an Annual Growth Rate percentage of 6.54%, especially in 2023 experiencing a significant increase. So based on the findings of the increasing trend of publications, it shows that more companies are integrating green accounting practices into their accounting systems and this practice helps improve the quality of financial reporting.